PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS SMART APPS CREATOR (SAC) TERHADAP MOTIVASI BELAJAR PADA MATA PELAJARAN IPAS SISWA KELAS IV SD NEGERI DOJA KABUPATEN GOWA - Minnafira; Abdul Rahman; Rahmawati Patta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the problem of low student learning motivation. The purpose of this study is to determine 1) the effect of using smart apps creator (SAC)-based learning media on learning motivation in the subject of science and social in grade IV students of SD Negeri Doja, Gowa Regency, 2) the perceptions of fourth-grade towards the use of smart apps creator (SAC)-based learning media in science and social learning. The approach used is quantitative with a pre-experimental design in the form of one-group pretest posttest design. The research sample was all fourth-grade students totaling 30 students with saturated sampling techniques. Data collection used learning motivation questionnaire instruments and student perception questionnaires, using descriptive statistical analysis techniques and non-parametric inferential statistics. The results of inferential statistical analysis using the Wilcoxon signed rank test obtained a calculated Zvalue greater than Ztable (4.785 > 1.96) and the Asymp.Sig value is smaller than the significance level (0.001 < 0.05), so that H1 is accepted and H0 is rejected, which means there is a significant difference in student learning motivation before and after being given treatment. The results of descriptive statistical analysis show that students’ perceptions are in the very good category (77%) and the good category (23%). Based on the research results, it can be concluded that smart apps creator (SAC) based learning media has an influence on learning motivation in the science and social subjects for fourth-grade students at SD Negeri Doja Kabupaten Gowa, and students have a relatively positive perception of the use of smart apps creator (SAC) based learning media.